Chitosan/Ce(IV) redox polymerization‐based amplification for detection of DNA point mutation. Issue 13 (2nd February 2016) - Zhuang, Dequan; Wen, Fei; Cui, Yanjun; Tan, Tianwei; Yang, Jing
ABSTRACT: Polymerization‐based signal amplification, a technique developed for use in rapid diagnostic tests, hinges on the ability to localize initiators as a function of interfacial binding events. We report here a new DNA detection method in which polymer growth in redox‐polymerization is used as a means to amplify detection signals. The introduction of biotin‐labeled chitosan (biotin‐CS) with highly dense amino groups into the polymerization amplification as macromolecular reducing agent, beneficially simplifies amplification operation, as well as, provides a large amount of initiation points to improve the sensitivity of detection. DNA hybridization, SA and biotin binding reactions led to the attachment of CS on a solid surface where specific DNA sequences were located. With the addition of the mixture containing monomer AM, crosslinker PEGDA and oxidant CAN onto the CS location, the growth of polymer films was triggered to render the corresponding spots readily distinguishable to the naked eye. Direct visualization of 0.21 fmol target DNA molecules of interest was demonstrated. Non‐small cell lung cancer p53 sequence was further selected as a proof‐of‐principle to detect DNA point mutation. The proposed method exhibited an efficient amplification performance for molecule detection, and paved a new way for visual diagnosis of biomolecules. © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2016, 54, 1929–1937 Abstract : Feasible and visual detection of DNA mutation was developed using redox polymerization with high‐molecular weight chitosan and Ce 4+ as an effective redox couple.